Canada’s Immigration Policies to Attract International Students - Gopal, Anita (International Higher Education, 2014)
This article highlights Canada’s flexible immigration and visa policies designed to increase international student enrollment. Such policies are a priority for all levels of the Canadian government and educational institutions since international students significantly bolster Canada’s economy with their skills and talent and serve as a remedy to current labor shortages. Flexible immigration policies provide Canada with a competitive edge over other major countries receiving international students, such as the U.S. and the U.K., where border controls are more restrictive.